Exploring the Relationship Between the Acceptability of an Internet-Based Intervention for Depression in Primary Care and Clinical Outcomes: Secondary Analysis of a Randomized Controlled Trial - Mira, Adriana; Soler, Carla; Alda, Marta; Baños, Rosa; Castilla, Diana; Castro, Adoración; García-Campayo, Javier; García-Palacios, Azucena; Gili, Margalida; Hurtado, Mariena; Mayoral, Fermín; Montero-Marín, Jesús; et al. (Frontiers in Psychiatry, 2019)
Depression is one of the most prevalent psychological disorders worldwide. Although psychotherapy for depression is effective, there are barriers to its implementation in primary care in Spain. The use of the Internet has been shown to be a feasible solution. However, the acceptability of Internet-based interventions has not been studied sufficiently . Objective: To assess the acceptability of an Internet-based intervention (IBI) for depression in primary care, and explore the relationship between expectations and satisfaction, and the improvement in the clinical variables in primary care patients. Furthermore, it offers data about the effects of sociodemographic characteristics on these acceptability variables and analyzes whether the expectations are related to finalizing the intervention. Data were based on depressive patients who were participants in a randomized controlled trial. We present the data from all the participants in the Internet intervention groups (N=198). They filled out the Expectation and Satisfaction Scales (6-item scales regarding treatment logic, satisfaction, recommending to others, Usefulness for other disorders, Usefulness for the patient, and unpleasantness), the Beck Depression Inventory II, and the secondary outcome measures : depression and anxiety, positive and negative affect. Results showed that participants’ expectations and satisfaction with the program were both high and differences in expectations and satisfaction depend on some sociodemographic variables (age: older people have higher expectations, and sex: women have greater satisfaction). A positive relationship between these variables and intervention efficacy was found: expectations related to “usefulness for the patient” was a statistically related predictor to the results on the BDI-II (Beta = 0.364) and the perception of how logic the treatment is (Beta = 0.528), was associated with change in the clinical variable. Furthermore, the higher the expectations, the higher improvements exhibited by the patients in all measures evaluated during the program. High expectations are directly related to finalizing the intervention. This is the first study in Spain to address this issue in the field of IBIs for depression in primary care. The IBI showed high acceptance related to the intervention’s efficacy and completion. Research on IBI acceptability could help to implement the treatment offered.